MANAGEMENT OF ROOT ROT AND GUMMOSIS IN NAGPUR MANDARIN (Journal of Plant Disease Sciences, 2023)
ABSTRACT Phytophthora nicotianae , a fungal pathogen, causes significant diseases such as root rot, crown rot, foot rot, gummosis, leaf fall, and brown rot in Nagpur mandarin and crop across the Vidarbha region of Maharashtra. Over three years, field trials conducted in Akola examined the impact of various conventional and one non conventional fungicide integrated with bio-agents on Phytophthora root rot and gummosis.The findings revealed that foliar application of potassium phosphonate (Potassium salt of phosphonic acid) at a concentration of 3 g/liter water demonstrated superior outcomes. This treatment resulted in an average reduction in lesion oozing by 32.31%, an increase in canopy volume by 19.22%, a minimal soil disease potential (18.0), least feeder root rot index of 0.98, and a higher fruit yield of 18.31 t/ha. Next best treatment was Dimethomorph (50WP) + Mancozeb (75WP) @ (1g + 2g/lit) tank mix application followed by soil application of harzianum Pseudomonas fluorescens+ (100g/plant each) with carrier material of FYM 1kg. The utilization of potassium phosphonate in mandarin cultivation has been advocated as a viable approach within integrated disease management strategies for effectively managing Phytophthora root rot and gummosis.
Keywords: Gummosis; Mandarin; Phytophthora; Management